Frequency-Dependent Viscoelastic Models for Passive Vibration Isolation Systems - Alberto Coronado; Marcelo A. Trindade; Rubens Sampaio (Shock and Vibration)
Even though there is a growing interest in active vibration isolation systems, passive approaches are still the best choice in many cases because they are inherently the simplest and of lowest cost. Moreover, better comprehension of the dynamics and specially of the damping behavior in passive systems is required for successful implementation of active schemes. In the vast literature of passive isolation systems, there are not many works that consider damping models more elaborated than the widely used complex modulus. In this work a passive isolation system composed of a base and two isolators, modelled as Timoshenko beams, and a vibration source, modelled as a rigid body, is considered. For the isolators, two different viscoelastic models are considered: the Anelastic Displacement Fields (ADF) and Fractional Calculus (FC), which will be compared with the complex modulus model. The results show that both ADF and FC models lead to better approximation of dissipated energy, since they account for frequency-dependence of the viscoelastic isolators. Analysis of the curve-fitting of material parameters, using ADF and FC models has shown that generally less parameters are needed by FC model, for the same fitting quality, although optimization results depends strongly on the initial guess for the solution.